INNOVATION OF DIGITAL IDENTITY APPLICATION (IKD) IN IMPROVING PUBLIC SERVICES IN GUNUNG ANYAR URBAN VILLAGE - Ananda Dwi Firdaus; Sri Wibawani (Fakultan Ilmu Sosial dan Ilmu Politik Universitas Tanjungpura, 2023)
The rapid development of technology requires Indonesia to continue to innovate in improving public services. ID card services are an important part of population services. But there are still some obstacles. So the Directorate General of Dukcapil of the Ministry of Home Affairs created a new innovation, namely the Digital Population Identity (IKD) application. Surabaya City has the highest number of IKD activation applicants in East Java Province. Including Gunung Anyar Village Office is a place for IKD activation, but there are still several obstacles. This study aims to analyze and describe the innovation of the Digital Population Identity (IKD) application in improving public services in Gunung Anyar Urban Village, Surabaya City. The research approach uses a qualitative descriptive method. The results of this study are 1) Relative advantages, in this case IKD has the advantage of utilizing technological developments to greatly benefit the efficiency of time in processing Digital ID cards so that it can create a sense of satisfaction to the public. 2) Compatibility, in this case IKD is in accordance with regulations and there is compatibility with previous innovations, namely the transformation from physical KTP to digital KTP. 3) Complexity, in this case indicating a challenge. Although the application is designed to be easy to operate, the activation process still requires adaptation from some communities, especially those less familiar with technology. 4) Demonstrated ability, in this case, IKD in Gunung Anyar Village has produced positive results. The trial was carried out in stages, starting from the ASN Dispendukcapil to all Gunung Anyar Village employees and residents who applied for KTP reprints. 5) Ability to be demanded, in this case the ease of use and the benefits generated can be seen from the increase in the number of IKD users in Gunung Anyar Village. In general, it can be concluded that IKD is well received by residents of Gunung Anyar Village. IKD with various benefits and advantages that make residents feel that public services are more efficient in accordance with technological developments so that they can improve public services in Gunung Anyar Village.